Analysing factors influencing the gross profit margin of informal food traders post Covid-19 pandemic in Polokwane Local Municipality, South Africa - Legong, Mokibelo Elsie (My University, 2025)
The informal food sector is a critical contributor to local economies, providing income opportunities, generating revenue, supporting livelihoods, and alleviating poverty. However, the COVID-19 pandemic and its associated lockdown restrictions significantly affected informal traders in South Africa, disrupting their livelihoods, economic activities and potentially affecting their profitability. While previous research has documented the pandemic's broader effects on informal traders, such as reduced income and challenges in accessing trading locations, it has not specifically examined how these disruptions impacted the gross profit margins of informal food traders post-pandemic. Hence, this study seeks to analyse factors influencing the gross profit margin of informal food trading post COVID-19 pandemic. The study aims to analyse the factors influencing the gross profit margin of informal food trading in selected areas of Polokwane Local Municipality post-COVID-19 pandemic. This aim is achieved through three research objectives, which are as follows. The first objective is to describe and identify the socio-economic characteristics of informal food traders. In addition, the second objective seeks to determine the gross profit margin of these traders in the post-COVID-19 period. Finally, the third objective aims to identify the socio-economic, physical, institutional, legal, and post-COVID-19-related factors influencing the gross profit margin of informal food traders in the aftermath of the pandemic. For the analysis, primary data were collected from 150 informal food traders within the Polokwane Local Municipality. The traders were selected using a purposive sampling method. Moreover, descriptive analysis, gross profit margin analysis, and Ordinary Least Squares (OLS) regression were used to analyse the data and achieve the first, second, and third objectives, respectively. Descriptive statistics revealed that 64% of informal food traders were women and 36% were men. The average age was 42 years, with a range from 27 to 60 years. Education levels averaged 8 years, with a minimum of 0 years (for those who never attended school) and a maximum of 17 years (for those with tertiary qualifications). Household size ranged from 2 to 14, with an average of 6 individuals. The average income of household heads was R3,314, with a minimum of R800 and a maximum of R9,000. The number of dependents ranged from 0 to 8, with an average of 3. Most respondents (71.3%) had no other sources of income, while 28.7% did. The average number of working days was 6, ranging from 5 to 7, and trading experience varied from 1 to 28 years, with an average of 7 years. The descriptive results further showed that nearly a quarter of the traders (24.7%) were selling prepared food, followed by those selling both fruits and vegetables (22.6%) and snacks (20.7%). Traders selling vegetables accounted for 16.7%, while those selling fruits made up 15.3%. The overall gross profit margin was 56%, implying that informal food trading was profitable post-COVID-19, as traders were able to generate revenue and cover operating costs. Informal vegetable traders achieved the highest gross profit margin of 60%, implying that vegetable traders had more efficient cost structures or higher mark-ups post COVID-19. Conversely, snacks traders experienced the lowest gross profit margin of 50%, which suggests a balance between the costs of goods sold and pricing strategies for their snacks. The OLS model results showed that age, household size, harassment, transport, and trading licence/permit negatively influenced the gross profit margin. Based on this, policy interventions should focus on combatting harassment, enhancing transport infrastructure, and simplifying trading license/permit processes. In contrast, the level of education, household head income, shelters used by informal food traders, and Social Relief of Distress (SRD) grant positively influenced the gross profit margin of informal food traders. Therefore, policy strategies should focus on improving income and access to education, providing trading infrastructure, and implementing SRD grants in a sustainable manner
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2025
Keywords: Profit; Gross Profit margin; Informal food traders; Post COVID-19 pandemic; Polokwane Local Municipality; Income -- South Africa; Informal sector (Economics) -- Law and legislation; Profit; COVID-19 (Disease); Street-food vendors (Persons)